Are There Places for Negotiation in Politics Regulation of Public School Quality? - Mara Regina Lemes de Sordi (Universidade Estadual Paulista Júlio de Mesquita Filho, 2010)
Describe the project of institutional Evaluation developed in municipal district educationemphasizing the guiding principles of the propose that values the local school actorsstrengthening for participate in the negotiation for a public school whose conception ofq u a l i t y i s s o c i a l l y r e l e v a n t . B y t h e a c t o r s v o i c e s e n g a g e d i n t h e p r o c e s s o fimplementation, the challenges, the capabilities and the vulnerabilities of the proposeare emphasized. Can be conclude that the institutional evaluation in elementary schoolsis an area under construction and needs a politic provision to try alternative modelswhere the regulation can occurs in a negotiated and participatory way.